On the Benefits of Semi-Active Suspensions with Inerters - Xin-Jie Zhang; Mehdi Ahmadian; Kong-Hui Guo (Shock and Vibration)
Inerters have become a hot topic in recent years especially in vehicle, train, building suspension systems, etc. Eight different layouts of suspensions were analyzed with a quarter-car model in this paper. Dimensionless root mean square (RMS) responses of the sprung mass vertical acceleration, the suspension travel, and the tire deflection are derived which were used to evaluate the performance of the quarter-car model. The behaviour of semi-active suspensions with inerters using Groundhook, Skyhook, and Hybrid control has been evaluated and compared to the performance of passive suspensions with inerters. Sensitivity analysis was applied to the development of a high performance semi-active suspension with an inerter. Numerical simulations indicate that a semi-active suspension with an inerter has much better performance than the passive suspension with an inerter, especially with the Hybrid control method, which has the best compromise between comfort and road holding quality.